Incidence rates of neurotropic-like and viscerotropic-like disease in three dengue-endemic countries: Mexico, Brazil, and Malaysia. Issue 13 (22nd March 2019) - Cohen, Carine; Moreira, Edson D.; Nañez, Homero; Nachiappan, Jeyaseelan P.; Arvinder-Singh, HS; Huoi, Catherine; Nealon, Joshua; Sarti, Elsa; Puentes-Rosas, Esteban; Moureau, Annick; Khromava, Alena; ,
Abstract: Background: The background incidence of viscerotropic- (VLD) and neurotropic-like disease (NLD) unrelated to immunization in dengue-endemic countries is currently unknown. Methods: This retrospective population-based analysis estimated crude and standardized incidences of VLD and NLD in twelve hospitals in Brazil (n = 3), Mexico (n = 3), and Malaysia (n = 6) over a 1-year period before the introduction of the tetravalent dengue vaccine. Catchment areas were estimated using publicly available population census information and administrative data. The denominator population for incidence rates was calculated, and sensitivity analyses assessed the impact of important assumptions. Results: Total cases adjudicated as definite VLD were 5, 57, and 56 in Brazil, Mexico, and Malaysia, respectively. Total cases adjudicated as definite NLD were 103, 29, and 26 in Brazil, Mexico, and Malaysia, respectively. Crude incidence rates of cases adjudicated as definite VLD in Brazil, Mexico, and Malaysia were 1.17, 2.60, and 1.48 per 100, 000 person-years, respectively. Crude incidence rates of cases adjudicated as definite NLD in Brazil, Mexico, and Malaysia were 4.45, 1.32, and 0.69 per 100, 000 person-years, respectively. Conclusions: Background incidence estimates of VLD and NLD obtained in Mexico, Brazil, and Malaysia could provide context for cases occurring after the introduction of the tetravalent dengue vaccine.